Broadening and shift coefficients for the (2←0) overtone band of HCl (1.76 µm) induced by exhaust gases CO and CO2. (December 2017) - Li, Gang; Domanskaya, Alexandra V.; Tran, Ha; Gisi, Michael; Ebert, Volker
Abstract: We present experimental data on the line pressure broadening and shift coefficients in the first vibrational overtone band of HCl in mixtures with CO and CO2 gas at room temperature. CO-broadening coefficients are published for the first time. The CO2 -broadening coefficients and shifts for both systems are in very good agreement with the literature data and have better accuracy than earlier results. Collisions with CO2 lead to stronger broadening for the most lines than collisions with CO. Similar to the broadening coefficients, the absolute values of CO2 -induced shift coefficients are larger than those for HCl-CO system. However, the asymmetric shifts are very similar for both systems except for R2 (0) and P2 (1) lines, where the interaction anisotropy has the strongest influence. Highlights: Experimental values for pressure broadening and shifts induced by collisions with CO and CO2 . Better accuracy than in earlier measurements. Broadening coefficients for HCl-CO system are presented for the first time.